PROTECTION OF THE SEA REGION FROM OIL POLLUTION BY TANKER SHIP - Kristiani Purwendah, Elly (Jurusan Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2020)
In the context of national law, Law Number 32 Year 2009 concerning Environmental Protection and Management (UUPPLH) provides an understanding of the environment as a unitary space with all objects, forces, and living things, including humans and their behavior, which affect nature itself, continuity of life, and the welfare of humans and other living things. Environmental protection has general principles, namely: Sovereignty over natural resources and the responsibility not to cause damage to the environment of other states or areas beyond national jurisdiction; Principle of preventive action; Cooperation; Sustainable development. Specifically the mandate of the 1945 Constitution is spelled out in the weighing section of Law Number 32 of 2009 concerning Protection of Environmental Management (UUPPLH) which states that a good and healthy environment is the human right of every Indonesian citizen as mandated in Article 28H of the Law 1945 Constitution of the Republic of Indonesia. This law states that environmental protection and management are systematic and integrated efforts undertaken to preserve environmental functions and prevent environmental pollution and / or damage which includes planning, utilization, control, maintenance, supervision and law enforcement.